2017
DOI: 10.1007/s00415-017-8596-7
|View full text |Cite
|
Sign up to set email alerts
|

What proportion of AQP4-IgG-negative NMO spectrum disorder patients are MOG-IgG positive? A cross sectional study of 132 patients

Abstract: Antibodies to myelin oligodendrocyte glycoprotein (MOG-IgG) have been described in patients with neuromyelitis optica spectrum disorders (NMOSD) without aquaporin-4 antibodies (AQP4-IgG). We aimed to identify the proportion of AQP4-IgG-negative NMOSD patients who are seropositive for MOG-IgG. In a cross sectional study, we reviewed all patients seen in the National NMO clinic over the last 4 years (after the availability of MOG-IgG testing), including clinical information, MRI, and antibody tests. 261 unique p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(137 citation statements)
references
References 10 publications
4
130
0
3
Order By: Relevance
“…Clinical studies investigating the role of MOG‐IgG in the pathogenesis of NMOSD are still emerging. Using highly sensitive cell‐based assays (CBAs), approximately 15–40% of patients with AQP4‐IgG‐seronegative NMOSD tested positive for MOG‐IgG, accounting for 6–20% of the total cohort of patients with NMOSD . Interestingly, patients with NMOSD who were seropositive for both antibodies (both AQP4‐IgG and MOG‐IgG) are rare, and only sporadic cases have been reported .…”
Section: Aqp4‐igg‐seronegative Nmosdmentioning
confidence: 98%
“…Clinical studies investigating the role of MOG‐IgG in the pathogenesis of NMOSD are still emerging. Using highly sensitive cell‐based assays (CBAs), approximately 15–40% of patients with AQP4‐IgG‐seronegative NMOSD tested positive for MOG‐IgG, accounting for 6–20% of the total cohort of patients with NMOSD . Interestingly, patients with NMOSD who were seropositive for both antibodies (both AQP4‐IgG and MOG‐IgG) are rare, and only sporadic cases have been reported .…”
Section: Aqp4‐igg‐seronegative Nmosdmentioning
confidence: 98%
“…45 Whether acute hemorrhagic leukoencephalitis is a variant of ADEM or separate entity remains controversial. [97][98][99] MOG-IgG positivity is found in patients who have previously been diagnosed with a variety of clinical phenotypes, such as ADEM, MS, optic neuritis and transverse myelitis. 22,59,91 Gadolinium enhancement is variable.…”
Section: Spinal Cord Lesionsmentioning
confidence: 99%
“…It has been reported that 21-42% of AQP4-IgG-negative NMOSD patients are MOG-IgG-positive. [97][98][99] MOG-IgG positivity is found in patients who have previously been diagnosed with a variety of clinical phenotypes, such as ADEM, MS, optic neuritis and transverse myelitis. 92,98,100,101 A significant percentage of patients previously diagnosed with multiphasic demyelinating encephalomyelitis and ADEM followed by optic neuritis are also MOG-IgG-positive.…”
Section: Mog Encephalomyelitis (Mog-igg Disease)mentioning
confidence: 99%
“…Previously considered a variant of multiple sclerosis, recognition of NMOSD as a separate clinical entity and its differential diagnosis was revolutionized by the discovery of a disease-specific, pathogenic immunoglobulin G (IgG) autoantibody directed against the aquaporin-4 water channel (AQP4) in the serum of ≈ 75-90% of patients. Detection of AQP4-IgG greatly facilitates accurate identification of new cases (less stringent diagnostic criteria apply in AQP4-IgG-seropositive patients) and prompt initiation of treatment [1,4,[7][8][9]. Interestingly, a sizeable minority of APQ4-IgG seronegative patients presenting with symptoms of NMOSD display an autoantibody against myelin oligodendrocyte glycoprotein (MOG); increasingly, MOG-IgG is being regarded as a potentially pathogenic biomarker for a similar, but separate, disease entity (anti-MOG syndrome), rather than for a subgroup of NMOSD patients [1,3,10].…”
Section: Introductionmentioning
confidence: 99%